Pemberian Makanan Pralaktasi dengan Kelangsungan Hidup Bayi di Indonesia - Utami Dewi; Siswanto Agus Wilopo; Tunjung Wibowo (JURNAL KESEHATAN REPRODUKSI, 2017)
Background: It is recommended for a mother to initiate to give early breastfeeding for a newborn as the first breast milk is known to be nutritious and contains antibody. The delay of breastfeeding shows that non breast milk-supplementary food is given. Based on BPS and Macro International data 65% of infants received pre-lacteal feeds besides breast milk in their three days of life.Objective: the known relationship between pre-lacteal feeds and infants’ survival in Indonesia.Method: This was an observational study with a cohort retrospective study design by using IDHS data year 2007. Samples were all infants (0-12 months, breastfed after birth) from mothers aged 15-49 years old as many as 2,886 mothers. The independent variable was pre-lacteal feeds after birth and the dependent variable was infants’ survival. The analyses used univariable, bivariable, and survival analysis with KaplanMeier, Log regression and Cox regression.Result and Discussion: Bivariable analysis using survival Kaplan-Meier showed that there was a significant relationship between pre-lacteal feeds after birth and infants’ survival. The survival of infants who received pre-lacteal feeds was greater than that of infants who did not receive pre-lacteal feeds (92%:89%). Multivariable analysis using Cox regression showed that the survival chance in infants who did not receive pre-lacteal feeds was 0.63 times lower than that in infants who received pre-lacteal feeds (HR 0.63; CI 95%=0.42-0.95).Conclusion: Pre-lacteal feeds showed a significant result with infant survival. Other factors affecting infant’s survival were mother’s age < 20 and ≥ 35 years, low economic status, and birth assistant with non professional.Keywords: infant’s survival, pre-lacteal feeds, infant